Fuzziness and medicine: philosophical reflections and application systems in health care : a Companion Volume to Sadegh-Zadeh's handbook of analytical philosophy of medicine - Tabacchi, Marco Elio (Studies in fuzziness and soft computing, 2013)
This book is a collection of contributions written by philosophers and scientists active in different fields, such as mathematics, logics, social sciences, computer sciences and linguistics. They comment on and discuss various parts of and subjects and propositions introduced in the Handbook of Analytical Philosophy of Medicine from Kazem Sadegh-Zadeh, published by Springer in 2012. This volume reports on the fruitful exchange and debate that arose in the fuzzy community upon the publication of the Handbook. This was not only very much appreciated by the community but also seen as a critical starting point for beginning a new discussion. The results of this discussion, which involved many different perspectives from science and the humanities and was warmly encouraged by Kazem Sadegh-Zadeh himself, are accurately reported in this volume, which is intended to be a critical companion to Kazem Sadegh-Zadeh´s handbook.   Rudolf Seising is currently an adjoint researcher at the European Centre for Soft Computing in Mieres, Asturias (Spain) and a college lecturer at the Faculty of History and Arts, at the Ludwig Maximilians University of Munich (Germany).   Marco Elio Tabacchi is currently the Scientific Director of the Italian National Research & Survey Organization Demopolis, and a research assistant in the Soft Computing Group at University of Palermo (Italy).